De la “Formación y rendimiento” a la “Formación y desarrollo” en la revista Capital Humano - Sánchez Valle, Ignacio (Revista Complutense de Educación, 2008)
The Spanish journal “Capital Humano” is almost twenty years old (1988-2008). This paper analyses the section “Training and Development” that is the new title from 2003 of “Training and efficiency” that began on 2000. This work analyses the content and try to interpret this change in denomination. Our methodology is used by the modern Documentation Science: analysis of content and indexing and abstract. We draw the conclusions from two tables with all information. The main conclusion is that is not remarkable differences in the change of “efficacy” by “development. The table number three makes clear this conclusion.